A genetic screen identifies TCF3/E2A and TRIAP1 as pathway-specific regulators of the cellular response to p53 activation - Andrysik, Zdenek (2013)
The p53 transcription factor participates in diverse cellular responses to stress including cell cycle arrest, apoptosis, senescence and autophagy. The molecular mechanisms defining the ultimate outcome to p53 activation remain poorly characterized. We performed a genome-wide genetic screen in human cells to identify pathway-specific coregulators of the p53 target genes CDKN1A (p21), an inhibitor of cell cycle progression, versus BBC3 (PUMA), a key mediator of apoptosis. Our screen identified numerous factors whose depletion creates an imbalance in the p21:PUMA ratio upon p53 activation. The transcription factor TCF3/E2A drives p21 expression while repressing PUMA across cancer cell types of multiple origins. Accordingly, TCF3/E2A depletion impairs the cell cycle arrest response and promotes apoptosis upon p53 activation by chemotherapeutic agents. In contrast, TRIAP1 is a specific repressor of p21 whose depletion slows down cell cycle progression. Our results reveal strategies to drive cells toward specific p53-dependent responses.